2019
DOI: 10.1016/j.jmig.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Cesarean Scar Pregnancy Successfully Treated via Hysteroscopy-Assisted Laparoscopy

Abstract: To evaluate the efficacy of hysteroscopy-assisted laparoscopy as a treatment strategy for type 2 cesarean scar pregnancy at gestational age >8 weeks. Design: Retrospective case series (Canadian Task Force classification II-3). Setting: A tertiary hospital. Patients: Eight women with type 2 cesarean scar pregnancy at a gestational age >8 weeks. Interventions: All patients underwent hysteroscopy-assisted laparoscopic resection and isthmus repair of cesarean scar pregnancy. Measurements and Main Results: All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Until now, there have been few studies on the treatment of CSP according to its classification. Our previous research shows that hysteroscopy-assisted laparoscopy is safe and effective for type 2 CSP (Qi et al, 2019), which has been confirmed by other similar studies (Wang et al, 2014;Shen et al, 2021). As the gestational sac is implanted on the scar and grows toward the uterine cavity, the risk of type 1 CSP is relatively lower, therefore, we evaluate the treatment of type 1 CSP based on the therapeutic effect and health economics.…”
Section: Discussionsupporting
confidence: 68%
“…Until now, there have been few studies on the treatment of CSP according to its classification. Our previous research shows that hysteroscopy-assisted laparoscopy is safe and effective for type 2 CSP (Qi et al, 2019), which has been confirmed by other similar studies (Wang et al, 2014;Shen et al, 2021). As the gestational sac is implanted on the scar and grows toward the uterine cavity, the risk of type 1 CSP is relatively lower, therefore, we evaluate the treatment of type 1 CSP based on the therapeutic effect and health economics.…”
Section: Discussionsupporting
confidence: 68%
“…A total of 358 articles were identified; 122 were assessed with respect to their eligibility for inclusion and 44 studies were included in the systematic review (Table 1, Figure 1). 9,10,21‐61 These studies included 3598 women with a prior CSP; of these, information on subsequent pregnancy was available for 592 women.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our case presents a different management method for this type of ectopic pregnancy - the use of Myosure hysteroscopy. The use of hysteroscopy for the treatment of this cesarean scar pregnancy has been cited a few times in the literature thus far [ 11 , 12 ]. The use of Myosure has been cited once for the management of cornual ectopic pregnancy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%